Global perspectives on green business administration and sustainable supply chain management - Khan, Syed Abdul Rehman, 1987- (Advances in logistics, operations, and management science (ALOMS) book series., 2020)
""This book discusses innovative green practices including recycling, remanufacturing, reduction in waste and adoption of renewable energy in manufacturing. It also examines environmentally friendly policies that have been adopted by many European and Western countries"--Provided by publisher"--